Antimicrobial effect of Moringa oleifera seed powder against Vibrio cholerae isolated from the rearing water of shrimp (Penaeus vannamei) postlarvae. (27th November 2021) - Flores, B.; Ramírez, E.; Moncada, A.; Salinas, N.; Fischer, R.; Hernández, C.; Mora‐Sánchez, B.; Sheleby‐Elías, J.; Jirón, W.; Balcázar, J.L.
Abstract: Shrimp farming has experienced rising costs as a result of disease outbreaks associated with Vibrio spp. Suitable strategies for disease prevention and control are therefore urgently needed. This study aimed to evaluate the antimicrobial effect of Moringa oleifera seed powder against Vibrio cholerae in the rearing water of Pacific white shrimp ( Penaeus vannamei ) postlarvae. In vitro assays included the determination of minimum inhibitory concentration (MIC) of M. oleifera seed powder against V . cholerae, whereas in vivo assays included the effect of M. oleifera seed powder on bacterial load and water quality parameters in the rearing tanks, as well as its effect on shrimp postlarvae survival. M. oleifera seed powder inhibited the growth of V. cholerae with MIC values of 62·5  µ g ml −1 . Moreover, seawater pH of treated tanks (8·66) was significantly lower ( P  < 0·01) than pH of the control tanks (9·02), whereas the visibility of treated tanks (37·08 cm) was significantly higher ( P  < 0·01) as compared to control tanks (35·37 cm). Likewise, V. cholerae load was significantly reduced ( P  < 0·01) from 4·7 × 10 4 to 3·1 × 10 3  CFU per ml in tanks treated with M. oleifera seed powder. Altogether, this study demonstrates the antimicrobial activity of M. oleifera against V. cholerae in shrimp culture. Abstract : Significance and Impact of the Study: A variety of Vibrio species are responsible for crustacean mortality during their early life stages, which have caused increased costs to the aquaculture industry. Effective control strategies are, therefore, urgently needed. In this study, in vitro and in vivo assays were performed to evaluate the antimicrobial activity of Moringa oleifera seed powder in the rearing water of Pacific white shrimp ( Penaeus vannamei ) postlarvae. M. oleifera seed powder exhibited a low minimum inhibitory concentration against Vibrio cholerae and significantly reduced the bacterial load. These results suggest that M. oleifera may offer an environmentally friendly and cost‐effective approach to control Vibrio infections.